The Indian Agro-Sector - vulnerable to Fragile Agro Policies - Kaibalya Manik, Bibhu; Puranjoy Ghosh, Dr. (International Journal of Engineering and Technology, 2019)
Lackadaisical proclivity in policy implementation and need-based developmental intervention in the agro-sector has sketched out its significance in 2018 States election in India. The evolving environment of global economic order influenced by the Liberalization of Trade, in addition, has posited the challenges about the requirement of more balanced approach in the legal framework of the country especially, for the agricultural sector. The agro-policy issues require discrete focus upon wide range of stakes of agricultural community, environmental, rural, and agribusiness communities of the country for shaping and augmenting: a) effective structural relationships with institutional framework and legal foundations relating to the stakeholders involved in production and marketing system to ensure better production operations to meet the sustaining food security of the country and global competition; b) visionary attempt to ensure adopting of environmental-friendly new technologies for the agro-production as well as scientific assurances considering consumersâ€™ concerns regarding food safety; c) renewed attention in the safety nets concerted in the legal frameworks relating to private sector risk management strategies, agricultural production, market-incentives, environmental amenities, public interest and private rights, etc.The National Commission on Farmers[i] for the faster and inclusive growth recommended varied scale of policy-transformation for enhancing, in particular small farm-income and the productivity, sustainability and to transfigure agricultural sector profitability. The present space, inter alia, has been used to analyze the recommendation of supply of credit â€“ aiming at strengthening the capital base of the small and marginal farmers of the country as enhancement of productivity necessarily implicates the increasing earnings of the farmers. The space has also been used to appraise the legal framework to economically incentivize the small and marginal farmers to assume the innovative climate-friendly technology to achieve sustainability, food security and integrated opportunities to meet the demands of agro market.The present appraisal, as stated above, has been attempted from the perspective of cost-risk-return of small and marginal farmers in India hence, the methodological approach is predominantly focused on the doctrinal and analytical one. The discourse is based on secondary data and statistics as available and could be collected from government records and relevant articles.Â Â Â